2020
DOI: 10.18332/tid/129266
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in waterpipe tobacco smoking among university students in four Eastern Mediterranean countries

Abstract: INTRODUCTION Males have a higher prevalence of waterpipe tobacco smoking (WTS) than females in most Eastern Mediterranean Region (EMR) countries, with a smaller gender gap than that of cigarette smoking. The objective of this study was to determine gender differences among university students with respect to WTS initiation, smoking behavior, tobacco flavors, and expenditure on WTS, in four EMR countries. METHODS A cross-sectional online survey was conducted based on convenient samples of ever waterpipe smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…When Jordanian pregnant women were asked about tobacco use addiction, the majority reported cigarettes as being addictive, whereas only 55.1% believed waterpipe to be addictive [ 28 ]. The misconception that waterpipe use is a healthy behavior, along with its social acceptability and lack of implemented anti-tobacco policies, were suggested to bridge the gap in waterpipe use between boys and girls and to fuel waterpipe use among girls around 2013 [ 20 , 44 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…When Jordanian pregnant women were asked about tobacco use addiction, the majority reported cigarettes as being addictive, whereas only 55.1% believed waterpipe to be addictive [ 28 ]. The misconception that waterpipe use is a healthy behavior, along with its social acceptability and lack of implemented anti-tobacco policies, were suggested to bridge the gap in waterpipe use between boys and girls and to fuel waterpipe use among girls around 2013 [ 20 , 44 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relative popularity among men can be related to the perception of smoking, in general, and waterpipe smoking, in particular, as a traditional masculine behavior (11). Among women university students, although the rates are lower than those observed in Eastern Mediterranean countries (30), they are still quite high (for example, 20% were current users (11) and 35% were ever users ( 12)).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of waterpipe smoking prevalence among university students in Arab countries showed that males had significantly higher rates than females in most of the countries, the highest rates for males being in Egypt, Jordan and Palestine 6 . Several studies showed further gender differences among university students in Arab countries with relation to prevalence 4 , to perception of harm 7 , WTS initiation and smoking behavior 8 , females showing higher levels of perceived harm and lower levels of heavy smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%